Detection of Alterations in the Gut Microbiota and Intestinal Permeability in Patients With Hashimoto Thyroiditis - Cayres, Leonardo César de Freitas; de Salis, Larissa Vedovato Vilela; Rodrigues, Guilherme Siqueira Pardo; Lengert, André van Helvoort; Biondi, Ana Paula Custódio; Sargentini, Larissa Donadel Barreto; Brisotti, João Luiz; Gomes, Eleni; de Oliveira, Gislane Lelis Vilela (Frontiers in Immunology, 2021)
Hashimoto thyroiditis (HT) is the most common autoimmune disease worldwide, characterized by chronic inflammation and circulating autoantibodies against thyroid peroxidase and thyroglobulin. Patients require hormone replacement with oral levothyroxine, and if untreated, they can develop serious adverse health effects and ultimately death. There is a lot of evidence that the intestinal dysbiosis, bacterial overgrowth, and increased intestinal permeability favor the HT development, and a thyroid–gut axis has been proposed, which seems to impact our entire metabolism. Here, we evaluated alterations in the gut microbiota in Brazilian patients with HT and correlated this data with dietary habits, clinical data, and systemic cytokines and zonulin concentrations. Stool samples from 40 patients with HT and 53 controls were analyzed using real-time PCR, the serum cytokine levels were evaluated by flow cytometry, zonulin concentrations by ELISA, and the dietary habits were recorded by a food frequency questionnaire. We observed a significant increase (p < 0.05) in the Bacteroides species and a decrease in Bifidobacterium in samples of patients with HT. In addition, Lactobacillus species were higher in patients without thyroid hormone replacement, compared with those who use oral levothyroxine. Regarding dietary habits, we demonstrated that there are significant differences in the consumption of vegetables, fruits, animal-derived proteins, dairy products, saturated fats, and carbohydrates between patients and control group, and an inverse correlation between animal-derived protein and Bacteroides genus was detected. The microbiota modulation by diet directly influences the inflammatory profile due to the generated microbiota metabolites and their direct or indirect action on immune cells in the gut mucosa. Although there are no differences in systemic cytokines in our patients with HT, we detected increased zonulin concentrations, suggesting a leaky gut in patients with HT. These findings could help understand the development and progression of HT, while further investigations to clarify the underlying mechanisms of the diet–microbiota–immune system axis are still needed.